Pelatihan Pembuatan dan Pengembangan Pupuk Organik Cair Biokultur dan Biourin untuk Mendukung Sistem Budidaya Sayuran Organik - Sri Anjar Lasmini; Idham Idham; Anthon Monde; Tarsono Tarsono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
In the development of vegetable farming by the community, there are fundamental problems which are generally carried out conventionally with the use of synthetic fertilizers and pesticides to determine the success of their farming. With the farming system, the community suffers a lot of losses because the inputs used are relatively expensive and on the other hand the products become cheap because the quality is not guaranteed. The solution to this problem is to develop bio-culture organic fertilizers and bio-urine whose raw materials are available in the region. The partner village development program aims to conduct training on the making and development of liquid organic fertilizer bio-culture and biourine to support the cultivation of organic vegetables. The method of approach applied is technology transfer (TT) and entrepreneurship capacity building (ECB) which is carried out with the Participatory Rural Approach (PRA) approach ) which in its implementation uses the method of lecture/discussion, training, making demo plotting, and assistance. The results achieved in the implementation of this program were that participants were able to make and develop liquid organic bioculture fertilizers and biourin and apply it to their farms as an alternative to chemical fertilizers